Westlake : poems by Wayne Kaumualii Westlake (1947-1984) - Westlake, Wayne (Talanoa., 2009)
In an all-too-brief life and literary career, Wayne Kaumualii Westlake (1947-1984) produced a substantial body of poetry. He broke new ground as a poet, translated Taoist classical literature and Japanese haiku, interwove perspectives from his Hawaiian heritage into his writing and art, and published his work locally, regionally, and internationally. Westlake was born on Maui and raised on the island of O'ahu, where he attended Punahou School, and later the University of Oregon. He earned his B.A. in Chinese studies at the University of Hawai'i. At the time of his tragic death in 1984, Westlake was at the height of his poetic career. Unfortunately, the only collection of his poems available at the time was a 32-page, limited edition chapbook independently published by a small press. The present volume, long overdue, includes nearly two hundred of Westlake's poems--most unavailable to the public or never before published.